Analysis for Hydrodynamic Wedge-Platform Thrust Slider Bearing with Ultralow Surface Separation - Chao Wang; Yongbin Zhang (International Journal of Rotating Machinery)
For the case of ultralow surface separation, in a hydrodynamic wedge-platform thrust slider bearing, the outlet zone and a portion of the inlet zone are in boundary lubrication, while most of the inlet zone is in the multiscale lubrication contributed by both the adsorbed boundary layer and the intermediate continuum fluid film. The present paper first presents the mathematical derivations for the generated pressure and carried load of this bearing based on the governing equation for boundary lubrication and the multiscale flow equation. Then, the full numerical calculation is carried out to verify the analytical derivations. It was found that the mathematical derivations normally have considerable errors when calculating the hydrodynamic pressure distribution in the bearing, owing to introducing the equivalent parameter λbf,e which is constant in the inlet zone; however they can be used to calculate the carried load of the bearing when the surface separation in the outlet zone is sufficiently high. The study suggests the necessity of the numerical calculation of the hydrodynamic pressure and even the carried load of this bearing. It is also shown that owing to the fluid-bearing surface interaction, the pressure and carried load of this bearing are significantly greater than those calculated from the classical hydrodynamic theory.